The dark side of ERP implementations: narratives of domination, confusion and disruptive ambiguity. (1st September 2014) - Kerr, Don; Houghton, Luke
Abstract : This paper explores end-user perceptions of poorly implemented enterprise resource planning systems (ERP) from the perspective of a primary frontline user. This exploration analyses three case studies – from Australia, the United Kingdom and Denmark. Through these cases, we find three areas of concern: the reaction of implemented systems to existing work processes; the suspicion among workers that management has a hidden agenda in implementing an ERP system; and the perception that the implemented system is poorly aligned and leads to process duplication. The objective of this research is to see how ERP implementations have consequences that go beyond current research which, in the main, frames ERPs in a positive light and does not critically evaluate them. Our research demonstrates that, while major work groups in an organisation may appear to accommodate the ERP implementation, many individuals are very concerned about how the ERP disrupts their work. Our research demonstrates that there may be 'dark' consequences arising from an ERP implementation. These are likely to include unauthorised software development to fit previous work processes, confusion and little understanding of the new business processes. The result is an overall lack of trust in the efficacy of the system.